Entry of cannabidiol into the fetal, postnatal and adult rat brain - Georgia Fitzpatrick; Yifan Huang; Fiona Qiu; Mark D. Habgood; Robert L. Medcalf; Heidi Ho; Katarzyna M. Dziegielewska; Norman R. Saunders (Cell and Tissue Research, 2024)
Cannabidiol is a major component of cannabis but without known psychoactive properties. A wide range of properties have been attributed to it, such as anti-inflammatory, analgesic, anti-cancer, anti-seizure and anxiolytic. However, being a fairly new compound in its purified form, little is known about cannabidiol brain entry, especially during development. Sprague Dawley rats at four developmental ages: embryonic day E19, postnatal day P4 and P12 and non-pregnant adult females were administered intraperitoneal cannabidiol at 10 mg/kg with [ 3 H] labelled cannabidiol. To investigate the extent of placental transfer, the drug was injected intravenously into E19 pregnant dams. Levels of [ 3 H]-cannabidiol in blood plasma, cerebrospinal fluid and brain were estimated by liquid scintillation counting. Plasma protein binding of cannabidiol was identified by polyacrylamide gel electrophoresis and its bound and unbound fractions measured by ultrafiltration. Using available RNA-sequencing datasets of E19 rat brain, choroid plexus and placenta, as well as P5 and adult brain and choroid plexus, expression of 13 main cannabidiol receptors was analysed. Results showed that cannabidiol rapidly entered both the developing and adult brains. Entry into CSF was more limited. Its transfer across the placenta was substantially restricted as only about 50% of maternal blood plasma cannabidiol concentration was detected in fetal plasma. Albumin was the main, but not exclusive, cannabidiol binding protein at all ages. Several transcripts for cannabidiol receptors were expressed in age- and tissue-specific manner indicating that cannabidiol may have different functional effects in the fetal compared to adult brain.